2020
DOI: 10.1055/a-1204-5443
|View full text |Cite
|
Sign up to set email alerts
|

Role of the KCNJ Gene Variants in the Clinical Outcome of Type 1 Diabetes

Abstract: Diabetes is considered as a disease with a wide and continuous clinical spectrum, ranging from Type 1 (T1D) and Type 2 Diabetes (T2D) with complex multifactorial causes. In the last years, particular attention has been focused on the predictive value and therapeutic potential of single nucleotide polymorphisms (SNPs). SNPs can alter the seed-sequence in miRNA’s loci and miRNA target sites cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
2
1
Order By: Relevance
“…In contrast to previous studies reporting an association of MODY genes and T1D susceptibility [13][14][15], in the present work, we did not find significant differences by comparing HNF1A SNPs frequencies between HC and T1D individuals.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies reporting an association of MODY genes and T1D susceptibility [13][14][15], in the present work, we did not find significant differences by comparing HNF1A SNPs frequencies between HC and T1D individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, there are numerous genes known to be involved in the predisposition to the development of T1D [12], but no effect of the HNFA1 gene is known. Moreover, very few studies have already reported a possible role in T1D of other genes involved in the development of rarest forms of MODY, namely NeuroD1 (MODY6), ABCC8 (MODY12), and KNCJ11(MODY13) genes [13][14][15]. In addition to T1D susceptibility, Blasetti et al [15] also found an association between rs5210 SNP in the KCNJ11 gene and clinical features of T1D, such as BMI at onset and insulin requirement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation